Relação entre a qualidade nutricional da liteira e a disponibilidade de nutrientes para as plantas em sucessão secundária na Amazônia Central - Mota, Maria do Socorro Souza da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2003)
The litter layer is the main responsible of soil fertility recovery and maintenance in Amazônia, through nutrient cycling and acting as a mechanical factor, protecting the soil from leaching and modifying soil moisture, temperature, nutritional status and light availability for the germination and establishment of seedlings. Knowledge of the relationships between the characteristics of resource qualily of the litter layer and the decomposition and nutrients release rates is veiy scarce, both for tropical mature forests and secondary growth. However, this knowledge is necessaiy to understand the djmamics of secondary succession, as well as to predict the effect of the introduction of selected tree species (fallow enrichment planting). The main objective of this study was to determine the effect of litter quality on the soil nutrient availability and processes of decomposition and mineralization the nutrients in the soil, as well as on decomposition rates in areas of secondary forest. To evatóate this, litter from different tree species [Hevea brasiliensis, Carapa guianensis, Vismia guianensis and the mixture of the three species), with different nutritional qualities, were added in areas of secondaiy forest. Decomposition rates, release of mineral nutrients and their effects on the germination and development of seedlings of Dinizia excelsa were measured. The same treatments were evaluated in an additional bexperiment conducted in a greenhouse. H. brasiliensis litter slowed faster weight loss and, consequently, larger release of nutrients into the soil, inrelation to the litter from C. guianensis and V. guianensis, in both experiments. However, better development of the test plants under the H. brasiliensis litter, considered as having the highest nutricional quality, was not found (either in the field cr in the greenhouse experiments). This indicates that the fundamental role of pioneer species in the recovery of secondaiy forest soils through the fallowing process, in this case for more than 7 years, masked the effects of the different litter types on the soil, and did not allow to find any significant differences among the treatments evaluated in the field. On the other hand, in the greenhouse experiment, V. guianensis litter showed better results for exchangeable bases and Ca, emphasizing that this species mobilizes nutrients that are fixed in the soil, such as Ca, and thus contributes to their availability to plants that establish themselves in secondary growth areas.
Keywords: Decomposição de liteira; Nutrição de plantas; Floresta secundária